Sintered body, method for manufacturing sintered body, member for plasma device, method for manufacturing member for semiconductor manufacturing device, semiconductor manufacturing device, and method for manufacturing semiconductor manufacturing device

By using high relative density and high hardness yttria fluoride sintered bodies, the problem of insufficient resistance to chemical and physical corrosion in semiconductor manufacturing equipment is solved, and higher corrosion resistance and lower dust generation are achieved.

JP7658887B2Active Publication Date: 2025-04-08SAMSUNG ELECTRONICS CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021199298
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-12-08
Publication Date
2025-04-08
Estimated Expiration
2041-12-08

AI Technical Summary

Technical Problem

The prior art has challenges in preventing chemical and physical corrosion in semiconductor manufacturing equipment, especially when using halogen-based etching gases, the corrosion resistance of corroded materials is insufficient.

Method used

A sintered body consisting of at least 50% of yttrium acid fluoride (Y5O4F7), with a relative density of 97.0% or higher, and a Vickers hardness of 5.0 GPa or higher, is used as a member of a semiconductor manufacturing device to improve its tolerance to chemical and physical corrosion.

Benefits of technology

It realizes effective protection of plasma corrosion in semiconductor manufacturing equipment, reduces the risk of chemical and physical corrosion, improves the durability and stability of the equipment, and reduces the amount of dust generation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658887000001
    Figure 0007658887000001
  • Figure 0007658887000002
    Figure 0007658887000002
  • Figure 0007658887000003
    Figure 0007658887000003
Patent Text Reader

Abstract

To provide a sintered body having high corrosion resistance, a method for manufacturing a sintered body, a member for a semiconductor manufacturing device, a method for manufacturing a member for a semiconductor manufacturing device, a semiconductor manufacturing device, and a method for manufacturing a semiconductor manufacturing device.SOLUTION: A sintered body according to an embodiment contains 50 [mass %] or more of yttrium oxyfluoride, has a relative density of 97.0 [%] or more, and has a Vickers hardness of 5.0 [GPa] or more. A method for manufacturing a sintered body according to an embodiment includes the steps of molding a molded body containing yttrium oxyfluoride powder having a particle size of 0.3 [μm] or less, and forming a sintered body by normal pressure sintering the molded body at 800°C or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sintered body, a method for manufacturing a sintered body, a member for a plasma device, a method for manufacturing a member for a semiconductor manufacturing device, a semiconductor manufacturing device, and a method for manufacturing a semiconductor manufacturing device. [Background technology]

[0002] As semiconductors become finer, there is a strong demand for low-contamination manufacturing processes. The impact of particles generated by dust in semiconductor manufacturing equipment, particularly plasma equipment, is becoming a serious problem. Examples of plasma equipment include dry etching equipment and plasma CVD equipment. Particles can be generated when etching gases and material gases, mainly halogen-based gases, corrode the inner walls and internal parts of a chamber. For this reason, corrosion resistance is required for components used in semiconductor manufacturing equipment, including plasma equipment. Until now, alumina has been used as a corrosion-resistant material. Recently, Yb, which has better corrosion resistance, has been used. 2 O 3 Technologies using yttrium oxide such as those mentioned above are becoming more and more practical.

[0003] In Patent Document 1 and Non-Patent Document 1, Y is used as a corrosion-resistant material. 5 O 4 F 7 Patent Document 1 and Non-Patent Document 1 disclose that a dense sintered body having a density of 99.0% or more can be obtained. [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] “Fabrication of dense yttrium oxyfluoride ceramics by hot pressing and their mechanical, thermal, and electrical properties”, Japanese Journal of Applied Physics 57, 06JF04 (2018) [Non-Patent Document 2] “Fluorine and oxygen plasma exposure behavior of yttrium oxyfluoride ceramics”, Japanese Journal of Applied Physics 58, SEEC01 (2019) [Non-Patent Document 3] "Development of low-dust generating materials with excellent plasma resistance", Ceramics 50 (2015) No.6 490-491 [Non-Patent Document 4] “CHARACTERISTICS OF KYOCERA FINE CERAMICS”, [online], Kyocera Corporation, [Retrieved November 1, 2021], Internet<https: / / www.kyocera.co.jp / prdct / fc / product / pdf / material.pdf> [Non-Patent Document 5] "Effect of rare earth additives on the transparency of α-SiAlON ceramics", Abstracts of the 33rd Autumn Symposium (lecture number 2F27) [Patent documents]

[0005] [Patent Document 1] JP 2016-098143 A Summary of the Invention [Problem to be solved by the invention]

[0006] Plasma erosion is driven primarily by two factors: chemical and physical.

[0007] Corrosion caused by chemical action progresses mainly through chemical reactions with the etching gas. The radicals generated when the etching gas is activated by plasma react chemically with the materials inside the chamber, resulting in corrosion. In order to suppress chemical corrosion, it is advisable to select a material that is less likely to react chemically with the etching gas as a corrosion-resistant material. From this perspective, rare earth compounds, such as Y 2 O 3 is selected. Rare earth compounds have low reactivity with halogen compounds that are generally used as etching gases. Furthermore, when a rare earth compound reacts with a halogen compound, the reactant, a rare earth halide, generally has a high boiling point and is therefore likely to remain on the surface of the components in the chamber. As a result, corrosion is unlikely to progress to the inside of the components in the chamber.

[0008] On the other hand, corrosion caused by physical action progresses mainly due to the sputtering action of the etching gas. The etching gas is ionized by the plasma, and the ions collide with the components in the chamber due to the potential difference, sputtering the components in the chamber, and corrosion caused by physical action progresses. Therefore, in order to develop a material with excellent corrosion resistance, it is important to consider both chemical and physical corrosion.

[0009] In Non-Patent Document 1, from the viewpoint of preventing chemical corrosion, Y 2 O 3 In Non-Patent Document 1, a material superior to Y is disclosed. 2 O 3 It has been pointed out that when a member containing yttrium is exposed to a plasma of a fluorine-based gas, a layer of deterioration due to fluorination is formed on the surface. 5 O 4 F 7 Since materials containing yttrium oxide and yttrium fluoride originally contain fluorine, such a deteriorated layer is unlikely to form. 2 O 3 It is expected to be a next-generation corrosion-resistant material that will replace Y.5 O 4 F 7 The material containing Y 2 O 3 It has been reported that the change in surface roughness before and after etching with halogen-based gas is smaller than that of materials containing Y. 5 O 4 F 7 The material containing Y 2 O 3 It has been suggested that the amount of particles generated is smaller and the size of the particles is smaller than that of materials containing yttrium oxyfluoride. 2 O 3 It can be said that this is superior to materials that contain

[0010] In Non-Patent Document 3, from the viewpoint of preventing physical corrosion, Y 2 O 3 According to Non-Patent Document 3, the results of evaluating the plasma resistance of Y by the AD method, which has a larger Vickers hardness, are disclosed. 2 O 3 However, it has been reported that the change in etching depth and surface roughness is small and the plasma resistance is high compared to other manufacturing methods. This result suggests that physical corrosion can be reduced if the hardness is high even for the same material.

[0011] A high hardness is also advantageous in terms of other aspects besides plasma resistance for semiconductor manufacturing equipment components. If the hardness is low, the surface is easily scratched during the assembly and maintenance of the equipment. If the resulting scratches are exposed to plasma, problems such as abnormal discharge and particle generation occur, which is undesirable.

[0012] In Non-Patent Document 2, Y 5 O 4 F 7 , Y 2 O 3 The results of measuring the etching depth of YOF before and after etching with halogen-based gases are also disclosed. 5 O 4 F 7It is expected that the etching depth of Y will be smaller, but no clear difference has been confirmed among the three materials. 2 O 3 On the other hand, Non-Patent Document 1 discloses that the Vickers hardness of Y 5 O 4 F 7 The Vickers hardness of Y is 0.491 GPa. 2 O 3 It has been disclosed that the value is smaller than that of Y 5 O 4 F 7 is Y 2 O 3 This suggests that chemical corrosion is smaller and physical corrosion is larger than that of Y. 5 O 4 F 7 and Y 2 O 3 This is thought to be the reason why the etching depths of the two samples were equivalent.

[0013] Furthermore, the dielectric tangent, or tan δ, which is one of the electrical properties, is also important for ceramics used in semiconductor manufacturing equipment components. When a component with a large tan δ value is placed in plasma, problems arise such as the loss of plasma uniformity, and the component generating heat due to Joule heat, affecting the temperature distribution. For example, Non-Patent Document 4 states that the value of tan δ at 1 MHz for alumina that is "for semiconductor device components" is 10×10 -4 In Non-Patent Document 1, the value of tan δ is disclosed, and the value is Y 5 O 4 F 7 For sintered bodies, it is 1.5×10 -4 , Y 5 O 4 F 7 +YF 3 For sintered bodies, it is 2.6×10 -4 Although sufficiently small values ​​were obtained, the Vickers hardness remained low at 0.491 GPa and 0.614 GPa, respectively.

[0014] Therefore, when the sintered body of yttrium oxyfluoride has high hardness, it is possible to obtain a semiconductor manufacturing equipment member having high plasma resistance and low dust generation. Furthermore, if the value of tan δ can be reduced, it is more preferable because the uniformity of the plasma can be ensured.

[0015] The present invention has been made in consideration of the above problems, and provides a sintered body, a method for manufacturing a sintered body, a member for semiconductor manufacturing equipment, a method for manufacturing a member for semiconductor manufacturing equipment, a semiconductor manufacturing equipment, and a method for manufacturing a semiconductor manufacturing equipment, which are capable of solving at least any of the various drawbacks described above. [Means for solving the problem]

[0016] The sintered body according to the first aspect of the embodiment of the present invention is It contains 50% or more by mass of yttrium oxyfluoride, has a relative density of 97.0% or more, and has a Vickers hardness of 5.0 GPa or more.

[0017] Moreover, the sintered body according to the first aspect of the embodiment of the present invention may further contain yttrium fluoride.

[0018] The sintered body according to the first aspect of the embodiment of the present invention may contain 10 mass % or less of at least one of a rare earth oxide, a rare earth fluoride, and a rare earth oxyfluoride.

[0019] The sintered body according to the first aspect of the embodiment of the present invention may have a relative density of 99.0% or more.

[0020] The crystal grains constituting the sintered body may have an average grain size of 1.15 μm or less.

[0021] The crystal grains constituting the sintered body may have an average grain size of 1.27 μm or less.

[0022] The dielectric tangent (tan δ) measured at 1 MHz is 10×10 -4 It may be the following.

[0023] A plasma device member according to a second aspect of the embodiment of the present invention uses the sintered body according to the first aspect of the embodiment of the present invention.

[0024] The plasma device member may be an edge ring, a shower nozzle, or a window.

[0025] A semiconductor manufacturing apparatus according to a third aspect of the embodiment of the present invention is configured to include the member for a plasma apparatus according to the second aspect of the embodiment of the present invention.

[0026] A method for producing a sintered body according to a fourth aspect of an embodiment of the present invention includes the steps of molding a molded body containing yttrium oxyfluoride powder having a particle size of 0.3 μm or less, and forming a sintered body by atmospheric sintering the molded body at 800° C. or less.

[0027] A method for producing a sintered body according to a fifth aspect of an embodiment of the present invention includes the steps of molding a molded body containing yttrium oxyfluoride powder and yttrium fluoride powder having a particle size of 0.5 μm or less, and forming a sintered body by atmospheric pressure sintering the molded body at 850° C. or less.

[0028] In a sixth aspect of the present invention, a method for producing a sintered body is provided, in which a raw material powder containing an yttrium oxyfluoride powder having a particle size of 0.5 μm or less is used, and a sintered body is formed by sintering the raw material powder at 850° C. or less by the SPS method.

[0029] The yttrium oxyfluoride powder may have a particle size of 0.3 μm or less, and may be sintered at 800° C. or less by the SPS method to form a sintered body.

[0030] In a seventh aspect of the present invention, a method for producing a sintered body is provided, in which a raw material powder containing an yttrium oxyfluoride powder and an yttrium fluoride powder having a particle size of 0.5 μm or less is used, and the raw material powder is sintered at 900° C. or less by the SPS method to form a sintered body.

[0031] In a method for producing a sintered body according to an eighth aspect of an embodiment of the present invention, a raw material powder containing yttrium oxyfluoride powder having a particle size of 0.5 μm or less is used, and a sintered body is formed by sintering the raw material powder at 850° C. or less by a hot press method.

[0032] The yttrium oxyfluoride powder may have a particle size of 0.3 μm or less, and may be sintered at 800° C. or less by the hot pressing method to form a sintered body.

[0033] A method for producing a sintered body according to a ninth aspect of an embodiment of the present invention uses raw material powder containing yttrium oxyfluoride powder and yttrium fluoride powder having a particle size of 0.5 μm or less, and sinters the raw material powder at 800° C. or less by a hot press method to form a sintered body.

[0034] The method for manufacturing a semiconductor manufacturing equipment member according to a tenth aspect of the present embodiment further comprises a step of manufacturing a sintered body using the method for manufacturing a sintered body according to any one of the fourth to ninth aspects of the present embodiment, and then applying the sintered body to a plasma equipment member.

[0035] The plasma device member may be an edge ring, a shower nozzle, or a window.

[0036] The method for manufacturing a semiconductor manufacturing equipment according to an eleventh aspect of the present embodiment further includes a step of manufacturing a semiconductor manufacturing equipment component using the method for manufacturing a semiconductor manufacturing equipment component according to the tenth aspect of the present embodiment, and then applying the semiconductor manufacturing equipment component to a semiconductor manufacturing equipment. Effect of the Invention

[0037] According to the present invention, it is possible to provide a sintered body having high corrosion resistance, a method for manufacturing a sintered body, a member for semiconductor manufacturing equipment, a method for manufacturing a member for semiconductor manufacturing equipment, a semiconductor manufacturing equipment, and a method for manufacturing a semiconductor manufacturing equipment. [Brief description of the drawings]

[0038] [Figure 1] 3 is a flowchart showing a method for producing a sintered body according to the first embodiment. [Diagram 2] 10 is a flowchart showing a method for producing a sintered body according to a second embodiment. [Diagram 3] 10 is a graph showing an example of a temperature and pressure profile in one step of the method for producing a sintered body according to the second embodiment. [Figure 4] 11 is a flowchart showing a method for producing a sintered body according to a third embodiment. [Diagram 5] 13 is a graph showing an example of a temperature and pressure profile in one step of the method for producing a sintered body according to the third embodiment. [Figure 6] FIG. 4 is a diagram showing the manufacturing conditions and evaluation results of a sintered body using the example of the manufacturing method of the sintered body according to the first embodiment. [Figure 7] FIG. 11 is a diagram showing the manufacturing conditions and evaluation results of a sintered body using the example of the manufacturing method of the sintered body according to the second embodiment. [Figure 8] FIG. 11 is a diagram showing the manufacturing conditions and evaluation results of a sintered body using the example of the manufacturing method of a sintered body according to the third embodiment. [Figure 9] FIG. 13 is a diagram showing the results of a plasma resistance test of sintered bodies produced using the examples of the manufacturing methods for the sintered bodies according to the first to third embodiments. [Figure 10] 1 is a graph showing peak intensities of powder X-ray diffraction of yttrium oxyfluoride according to ICDD (International Centre for Diffraction Data). [Figure 11] 13 is a flowchart showing a method for manufacturing a semiconductor manufacturing equipment member according to a fourth embodiment. [Figure 12] 13 is a flowchart showing a manufacturing method of a semiconductor manufacturing apparatus according to a fifth embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0039] (Embodiment 1) The sintered body and the method for manufacturing the sintered body according to the first embodiment will be described below with reference to FIG.

[0040] <Overview of sintered body> The sintered body according to the first embodiment contains 50% by mass or more of yttrium oxyfluoride, has a relative density of 97.0% or more, and has a Vickers hardness of 5.0 GPa or more. The yttrium oxyfluoride is Y x O y F z It can be expressed as (x ≠ y ≠ z), where x, y, and z may be set arbitrarily. It is preferable that y is smaller than x, and the value of z / y is 1.5 to 1.75. It is preferable that the crystal system is an orthorhombic system. In addition, the oxyfluoride of yttrium is, for example, Y 5 O 4 F 7 , Y 6 O 5 F 8 , Y 7 O 6 F 9 , Y 17 O 14 F 23 , and Y 1 O 0.826 F 1.348 The sintered body contains 50% by mass or more of yttrium oxyfluoride. 2 O 3 The sintered body has low chemical corrosion compared to sintered bodies containing . The sintered body has a relative density of 97.0% or more and few voids, so it has good plasma resistance. The sintered body has a Vickers hardness of 5.0 GPa or more, so it has good plasma resistance and is less susceptible to scratches on the surface. For these reasons, the sintered body has high corrosion resistance.

[0041] <Method of manufacturing sintered body by normal pressure sintering> The raw material powder is prepared (step ST11). The raw material powder is, for example, Y 5 O 4 F 7 Powder or Y 5 O 4 F 7 and Y.F. 3The particle size is, for example, 0.3 μm to 0.5 μm. 5 O 4 F 7 and Y.F. 3 The weight ratio of the mixed powder is set to a predetermined value. 5 O 4 F 7 The powder is a type of yttrium oxyfluoride powder. 5 O 4 F 7 The details of the yttrium oxyfluoride powder will be described later. The "particle size" of the raw material powder refers to the "median diameter (D50)" of the primary particle size measured using a particle size distribution measuring device based on a laser diffraction / scattering method, such as the MT3300 manufactured by MICROTRAC.

[0042] Next, the raw material powder is adjusted to obtain a powder for pressing (step ST12). The raw material powder, a solvent, a dispersant, and a binder are mixed to generate a binder-added slurry. The binder-added slurry is freeze-dried or spray-dried, for example, to remove the solvent from the binder-added slurry. Then, the powder for pressing is obtained.

[0043] Next, the powder for pressing is press molded to obtain a molded body (step ST13). Specifically, for example, the powder for pressing is placed in a metal mold. A hydraulic press is used to apply pressure to the powder for pressing to form a molded body. Then, the molded body is obtained by removing it from the metal mold.

[0044] Next, the molded body is subjected to a CIP (cold isostatic pressing) process (step ST14). The CIP process may be omitted in some cases.

[0045] Next, the CIP-treated molded body or the press-molded molded body is degreased by a method such as heating to remove the binder components (step ST15).

[0046] Finally, the degreased molded body is sintered under atmospheric pressure to produce a sintered body (step ST16). Specifically, the degreased molded body is heated in a predetermined gas atmosphere (predetermined flow rate) at a predetermined temperature for a predetermined time. The degreased molded body may be placed in an alumina crucible, the alumina crucible may be covered, and sintered under various conditions using an electric furnace. The sintering conditions may be, for example, a vacuum atmosphere (approximately 10 -3 The pressure may be set to 1000°C / h (in the Pa range), the heating rate may be set to 1000°C / h, the holding temperature may be set to 750 to 1000°C, the holding time may be set to 1 to 10 hours, and the temperature drop rate may be set to furnace cooling. The upper limit of the holding temperature range may be selected from 850°C, 825°C, or 800°C.

[0047] (Embodiment 2) <Method of manufacturing sintered body by spark plasma sintering> Next, a method for producing a sintered body according to the second embodiment will be described with reference to FIGS.

[0048] Raw material powder is prepared (step ST21). Step ST21 is the same as step ST11.

[0049] Next, the prepared raw material powder is spark plasma sintered to produce a sintered body (step ST22). "SPS (Spark Plasma Sintering) method" is an abbreviation of spark plasma sintering. The workpiece is sintered by mechanical pressure and pulse current heating. In general, sintering by the SPS method can densify at a low temperature in a short time, and it is said that it can suppress grain growth and increase density. Specifically, the raw material powder is put directly into a mold and sintered under various conditions using an SPS device. The sintering conditions are the atmospheric pressure, the temperature rise rate, the holding temperature, the holding time, the temperature fall rate, and the holding pressure. An example of the temperature and pressure profile in one step of the manufacturing method of the sintered body according to the second embodiment (Example 4 to be described later) is shown in FIG. 3. The holding temperature range may be set to, for example, 750 to 1000°C. The upper limit of the holding temperature range may be selected from 0°C, 850°C, or 800°C.

[0050] (Embodiment 3) <Method of manufacturing sintered body by hot press molding> Next, a method for producing a sintered body according to the third embodiment will be described with reference to FIGS.

[0051] Raw material powder is prepared (step ST31). Step ST31 is the same as step ST11 and step ST21.

[0052] Next, the raw material powder is primarily molded (step ST32). Specifically, the raw material powder is placed directly into a metal mold. Pressure is applied to the raw material powder using a hydraulic press to form a primary molded body. The primary molded body is removed from the metal mold. Note that the primary molded body may be left in the metal mold and used for the next hot press molding.

[0053] Finally, the primary molded body is hot-pressed (HP) to form a sintered body (step ST33). Specifically, the primary molded body obtained in step ST32 is placed in a hot press mold of the same size and hot-pressed using a molding device under various conditions. The hot press conditions include atmospheric gas, pressure, heating rate, holding temperature, holding time, heating rate, holding pressure, etc. An example of a temperature and pressure profile in one step of the manufacturing method for a sintered body according to the third embodiment (Example 13 to be described later) is shown in FIG. 5. The holding temperature may be set to, for example, 700 to 1000°C. Specifically, the upper limit of the holding temperature range may be selected from 850°C, 800°C, 780°C, 750°C, or 700°C. EXAMPLES

[0054] Next, the results of evaluation of a sintered body produced using the production method for the sintered body will be described with reference to Fig. 6 to Fig. 9. The production conditions for the sintered body, the evaluation method for the sintered body, and the evaluation results for the sintered body will be described in this order.

[0055] <Production conditions for sintered body> <1. Manufacturing conditions for sintered bodies by normal pressure sintering> The manufacturing conditions for the method for producing a sintered body by normal pressure sintering will be described. The method for producing a sintered body by normal pressure sintering has the same configuration as the method for producing a sintered body according to the first embodiment.

[0056] In step ST11, Y 5 O 4 F 7 Two types of powder were used: one with a particle size of 0.3 μm (hereinafter referred to as raw powder A) and one with a particle size of 0.5 μm (hereinafter referred to as raw powder B). 5 O 4 F 7 and Y.F. 3 Mixture of powder of one type, Y 5 O 4 F 7 and Y.F. 3 A powder with a particle size of 0.5 μm (hereinafter referred to as raw material powder C) was used, which was a mixture of these powders in a weight ratio of 60:40.

[0057] In step ST12, 50 g of raw material powder A, 25 g of pure water as a solvent, 0.3 g of Toagosei's A-30L as a dispersant, and 4.4 mL of a solution in which 3 mL of Toagosei's AS-1100 as a binder was dissolved in 12 mL of pure water were mixed in a glass container. This solution was freeze-dried to remove the pure water, and a powder for pressing was obtained. Raw material powders B and C were prepared in the same manner to obtain powders for pressing.

[0058] In step ST13, 8.0 g of the powder for pressing was first placed in a cylindrical mold having a diameter of 25 mm. A pressure of 25 MPa was applied to the powder for pressing using a hydraulic press machine to form a molded body. This molded body was obtained by removing it from the mold. The obtained molded body was, for example, a cylindrical body having a diameter of about 25 mm and a height of about 5.5 mm.

[0059] In step ST14, the molded body was vacuum-packed and then pressurized at a pressure of 300 MPa for 10 minutes using an isostatic pressurizing device Dr CIP manufactured by KOBELCO.

[0060] In step ST15, the CIP-treated molded body was placed on an alumina dish and degreased, to remove the binder and dispersant components contained in the molded body.

[0061] In step ST16, the degreased molded body is placed in an atmosphere of N 2 The degreased molded bodies were placed in an alumina crucible, which was then covered with a lid and sintered in an electric furnace. The sintering conditions were, for example, a vacuum atmosphere (approximately 1×10 -3 The temperature was set to 1 Pa, the heating rate was 1000°C / h, the holding temperature was 750 to 1000°C, the holding time was 1 to 10 hours, and the temperature drop rate was furnace cooling.

[0062] <2. Manufacturing conditions of sintered bodies by spark plasma sintering> Next, manufacturing conditions of an example of a method for manufacturing a sintered body by spark plasma sintering will be described. The method for manufacturing a sintered body by spark plasma sintering has the same configuration as the method for manufacturing a sintered body according to the second embodiment.

[0063] In step ST21, raw material powder A, raw material powder B, and raw material powder C were used as raw material powders, similarly to step ST11 in the example of the method for producing a sintered body according to the above-mentioned embodiment 1.

[0064] In step ST22, 6.4 g of raw material powder A was placed in a cylindrical mold with a diameter of 20 mm, and sintered under various conditions using an SPS device (Fuji Electric Power Industries, SPS-515). The sintering conditions were set as follows: in vacuum (approximately 3 Pa) or Ar (argon) gas (flow rate 1 L / min), heating rate 10-100°C / min, holding temperature 750-1000°C, holding time 0-1 hour, cooling rate 2-50°C / min up to 200°C, furnace cooling below 200°C, pressure increase started simultaneously with the start of heating and reached the holding pressure in 1 minute, holding pressure 40 MPa, decompression started simultaneously with the end of temperature holding, and decompression ended at a temperature of 200°C. Sintered bodies were obtained for raw material powders B and C in the same manner.

[0065] <3. Manufacturing conditions of sintered body by hot press molding> Next, manufacturing conditions of an example of a method for manufacturing a sintered body by hot press molding will be described. The method for manufacturing a sintered body by hot press molding has the same configuration as the method for manufacturing a sintered body according to the third embodiment.

[0066] In step ST31, raw material powder A, raw material powder B, and raw material powder C were used as raw material powders, similarly to step ST11 in the example of the method for producing a sintered body according to the above-mentioned embodiment 1.

[0067] In step ST32, 55 g of raw material powder A was placed directly into a cylindrical die with a diameter of 52 mm. A pressure of 18.4 MPa was applied to raw material powder A using a hydraulic press to form a primary molded body. The primary molded body was removed from the die and obtained. The primary molded body was an approximately cylindrical body with a diameter of approximately 52 mm and a height of approximately 12 mm. Primary molded bodies were obtained similarly for raw material powders B and C.

[0068] In step ST33, the primary molded body obtained in step ST32 was placed in a carbon hot press mold of the same size and hot-press molded under various conditions using a molding device HP-10X10-CC-23 manufactured by Nemus Co., Ltd. The hot press conditions were a vacuum atmosphere (approximately 10 -3 The conditions were as follows: in a 1 Pa atmosphere, or Ar gas (flow rate 1 L / min), the heating rate was 10°C / min, the holding temperature was 700 to 1000°C, the holding time was 1 to 5 hours, the heating rate was 10°C / min, the pressure increase started simultaneously with the start of the heating, the holding pressure was reached in 1 hour, the holding pressure was 36.7 MPa, the reduction in pressure was 0 MPa in 1 hour, and the reduction in pressure and the end of the temperature reduction were simultaneous.

[0069] <Evaluation method of sintered body> Next, the evaluation methods for the sintered body will be described. First, the evaluation methods will be described as follows: 1. density, 2. hardness (Vickers hardness), 3. whiteness, 4. composition analysis, and 5. plasma resistance.

[0070] <1. Density> The weight of the obtained sintered body in air and in pure water is measured using an electronic balance, and the density is calculated using Archimedes' method. The calculated density is taken as the theoretical density of the sintered body (Y 5 O 4 F 7 Theoretical density: 5.140g / cm 3 , Y.F. 3 Theoretical density: 5.063g / cm 3 The relative density (%) was calculated by dividing the calculated density by the mass fraction (molecular weight) by the mass fraction (density).

[0071] In addition, if there are voids in the materials used for semiconductor manufacturing equipment components, those areas will corrode intensively and become a source of dust. Therefore, materials used for semiconductor manufacturing equipment components are generally required to have a high relative density of 97.0% or more, and preferably 99.0% or more.

[0072] <2. Vickers hardness> The Vickers hardness was measured at a test force of 0.5 gf using a Mitutoyo Micro Vickers hardness tester HM-220.

[0073] <3. Electrical characteristics (dielectric tangent, tan δ)> The upper and lower surfaces of the sintered body were polished with #1000 waterproof paper. Then, tan δ was measured by the electrostatic capacitance method using a measurement system consisting of a Keysight impedance analyzer 4294A connected to a Keysight test fixture 16455B. -4 Because the measurements of tan δ were unstable in the smaller region, the value of tan δ in this region is listed as "< 1x10 -4 " was written.

[0074] <4. Impurities> Impurities in the sintered bodies were confirmed using a RIGAKU XRD (X-ray analysis device) SmartLab.

[0075] <5. Grain size of sintered body> The produced sintered body was broken with a hammer, and the cut surface was observed using a SEM (Hitachi scanning electron microscope, SU8000). The grain size (average intercept length La) was obtained from the SEM image using the intercept method, and the grain size was multiplied by 1.62 to obtain the grain size (average crystal grain size D). Specifically, in the SEM image developed on the XY plane, three lines were drawn at equal intervals in the XY direction, for a total of nine lines with a total length of L, and the number n of grains that each of these lines crossed was determined, and the average intercept length La and average crystal grain size D were calculated using the following relational equation. La = L / n D=1.62×La

[0076] <6. Plasma resistance test> First, to make the surface smooth and to make the variation between samples uniform, the surface of the sintered body was polished using waterproof paper of #1000 to #4000 until the arithmetic surface roughness (Ra) was approximately 0.1 um or less. Next, to ensure that there was an area that was not exposed to the plasma treatment, approximately half of the surface of the sintered body was covered with polyimide tape. The sintered body with the polyimide tape attached was then etched using an inductively coupled plasma (ICP) etcher manufactured by SELVAC, and CF 4 / O 2 A plasma resistance test was carried out using mixed gas. Specifically, the electrode size was 300 mm in diameter, the pressure was 1 Pa, the ICP power was 1500 W, the bias power was 170 W, and the CF 4 Gas flow rate was 180 mL / min, O 2 The gas flow rate was set to 45 mL / min, and the plasma treatment was performed for 50 hours. After the plasma treatment, the sintered body was taken out and the polyimide tape was peeled off.

[0077] The step of the boundary part near the end face of the polyimide tape was measured using a stylus-type surface profiler Surfcom1400G manufactured by Tokyo Seimitsu Co., Ltd., and the step was taken as the amount of etching. In addition, for the part not covered with the polyimide tape, the arithmetic surface roughness (Ra) of the sintered body surface was measured using the surface profiler before and after the plasma resistance test, and the deterioration rate of Ra was calculated using the following formula. (Ra deterioration rate) = (Ra after plasma resistance test) / (Ra before plasma resistance test)

[0078] When a member for semiconductor manufacturing equipment is exposed to plasma, a part of the member falls off from the surface of the member, generating particles. The size of the particles increases as the surface roughness of the member increases. In other words, a smaller surface roughness of the member is preferable because it is possible to reduce the size of the generated particles. Therefore, even if the etching amount does not change, it can be said that the smaller the rate of deterioration of Ra, the less the impact of particle generation due to plasma exposure.

[0079] <Evaluation results of sintered bodies> Next, the evaluation results of the sintered bodies are explained. The evaluation results are as follows: 1. Evaluation results of sintered bodies by normal pressure sintering, 2. Evaluation results of sintered bodies by spark plasma sintering, 3. Evaluation results of sintered bodies by hot press molding, and 4. Evaluation results of plasma property test of the sintered bodies.

[0080] <1. Evaluation results of sintered bodies obtained by normal pressure sintering> Fig. 6 shows the manufacturing conditions and evaluation results of the sintered bodies produced by the example of the manufacturing method of the sintered body based on the normal pressure sintering. Specifically, Fig. 6 shows the manufacturing conditions and evaluation results of the sintered bodies produced in Examples 1 to 3 and Comparative Examples 1 to 4.

[0081] Comparing Example 1, in which raw material powder A with a particle size of 0.3 μm was used and sintered at 800° C., with Comparative Example 1, in which raw material powder B with a particle size of 0.5 μm was used and sintered at 900° C., the density and hardness of Example 1 are greater, despite the lower sintering temperature. This is thought to be because when the raw material powder has a smaller particle size, densification proceeds at a lower temperature, resulting in greater density and hardness.

[0082] When comparing Comparative Example 1 and Comparative Example 4, in which raw material powders B and C were sintered under the same conditions, the density and hardness of Comparative Example 4 were greater. This is because YF 3 It is believed that the addition of lowered the sintering temperature and increased the density, resulting in increased hardness.

[0083] In Example 1, raw material powder A having a particle size of 0.3 μm was used and sintered at 800° C., and the Y 5 O 4 F 7 Sintered bodies were obtained. Since densification proceeds at lower temperatures when the grain size is made smaller, it is clear that if the grain size is made smaller than 0.3 μm, a sintered body with a relative density of 99.0% or more and a hardness of 6.0 GPa or more can be obtained even at a sintering temperature of 800° C. or less. Furthermore, the tan δ values ​​of the sintered bodies in these examples were all less than 1×10 -4 If the hardness of a sintered body follows the so-called Hall-Petch law, it is believed that the smaller the grain size, the greater the hardness, and it can be seen that in order to achieve a hardness of 6.0 GPa or more, the grain size should be at least 0.60 μm or less.

[0084] In Comparative Example 1, in which raw material powder B was used and sintered at 900°C, the tan δ value was small, but the relative density and hardness were insufficient. In order to increase the density, it is necessary to increase the sintering temperature, but according to the Hall-Petch law, the hardness is likely to decrease as grain growth progresses. Therefore, it seems difficult to obtain a sintered body with sufficiently high relative density and hardness by sintering raw material powder B at normal pressure.

[0085] YF 3 In Examples 2 and 3, raw material powder C containing added Y was sintered at 825 to 850°C, and the relative density was 99.0% or more and the hardness was 5.0 GPa or more. 5 O 4 F 7Sintered bodies were obtained. Since densification proceeds at lower temperatures when the grain size is smaller, it is clear that if the grain size of the raw material powder is made smaller than 0.5 μm, sintered bodies with a relative density of 99.0% or more and a hardness of 5.0 GPa or more can be obtained even in a temperature range lower than 825 to 850°C. Furthermore, the tan δ values ​​of the sintered bodies in these examples were all less than 1×10 -4 The density and tan δ values ​​of Comparative Example 4, which was sintered at 900°C using raw material powder C, were good, but the hardness was insufficient at less than 5.0 GPa. The grain size of Comparative Example 4 was larger than those of Examples 1 and 2. This is probably because the grain growth was promoted by the higher sintering temperature, resulting in a decrease in hardness. It can be seen that in order to achieve a hardness of 5.0 GPa or more, the grain size should be at least 1.27 μm or less.

[0086] Focusing on the tan δ of Examples 1 to 3 and Comparative Examples 1 to 4, sufficiently small values ​​were obtained except for Comparative Example 2, which had a low density. -4 It can be seen that in order to achieve this, the density must be at least 96.3% or higher.

[0087] As a result of XRD analysis of the sintered bodies of Examples 1 to 3 and Comparative Examples 1 to 4, the orthorhombic Y crystals were obtained from the sintered bodies using the raw material powder A and the raw material powder B. 5 O 4 F 7 Only the orthorhombic Y phase was observed in the sintered compact using raw powder C. 5 O 4 F 7 and orthorhombic YF 3 Only the phases were detected, and no impurities were observed.

[0088] As shown in FIG. 6, the sintered bodies according to Examples 1 to 3 and Comparative Examples 1 to 4 were judged as “poor” (×) if the density was less than 97.0% or the hardness was less than 5.0 GPa, as “good” (◯) if the density was 97.0% or more and less than 99.0% and the hardness was 5.0 GPa or more, or as “density was 99.0% or more and the hardness was 5.0 GPa or more and less than 6.0 GPa, and as “excellent” (◎) if the density was 99.0% or more and the hardness was 6.0 GPa or more.

[0089] <2. Evaluation results of sintered bodies produced by spark plasma sintering> Fig. 7 shows the manufacturing conditions and evaluation results of the sintered bodies produced by the example of the manufacturing method of the sintered body by spark plasma sintering. Specifically, Fig. 7 shows the manufacturing conditions and evaluation results of the sintered bodies produced in Examples 4 to 11 and Comparative Examples 5 to 7.

[0090] Comparing Example 6 with Comparative Example 6, and Example 9 with Example 10, which are combinations of raw material powder A and raw material powder B sintered under the same conditions, Example 6 and Example 9, which used raw material powder A, have higher density and hardness. This is thought to be because the raw material powder has a small particle size, which allows the sintering temperature to be lowered, resulting in a higher density.

[0091] Comparing Comparative Example 7 and Example 11, in which raw material powders B and C were sintered under the same conditions, raw material powder C had a higher density and hardness and a smaller grain size. This is because YF 3 It is believed that the addition of ZnO resulted in a lower sintering temperature, suppressing grain growth while densifying the material, thereby increasing density and hardness.

[0092] Raw material powder A was used and sintered at 800 to 850°C in a vacuum atmosphere. In Examples 4 to 7 and Example 9, Y had a relative density of 99.0% or more and a hardness of 6.0 GPa or more. 5 O 4 F 7 In addition, a sintered body having a relative density of 99.0% or more and a hardness of 5.0 GPa or more was obtained by sintering raw material powder A at 800° C. under an Ar atmosphere in Example 8. 5 O4 F 7 It is clear that if the grain size of the raw material powder is made smaller than 0.3 μm, a sintered body with a relative density of 99.0% or more and a hardness of 6.0 GPa or more can be obtained even in a temperature range lower than 800 to 850°C. Furthermore, the tan δ value of the sintered bodies in these examples was 1×10 -4 The results were good, being as small as or less. It can be seen that in order to achieve a hardness of 6.0 GPa or more, the grain size should be at least 1.05 μm or less, and in order to achieve a hardness of 5.0 GPa or more, the grain size should be at least 1.15 μm or less. From the results of Example 8, it can be seen that sintered bodies having sufficiently high relative density and hardness and small dielectric loss tangent can be obtained not only in a vacuum atmosphere but also in an Ar atmosphere.

[0093] In Example 10, raw material powder B was used and sintered at 850° C., and the Y according to the present disclosure had a relative density of 97.0% or more and a hardness of 5.0 GPa or more. 5 O 4 F 7 A sintered body was obtained. It is clear that if the grain size of the raw material powder is made smaller than 0.5 μm, a sintered body with a relative density of 97.0% or more and a hardness of 5.0 GPa or more can be obtained even in a temperature range lower than 850°C. Furthermore, the tan δ value of the sintered body according to this embodiment is 1×10 -4 The grain size was small and favorable, being less than 0.86 μm. It can be seen that in order to achieve a hardness of 5.0 GPa or more, the grain size should be at least 0.86 μm or less. In Comparative Example 6, in which the sintering temperature was lower than that of Example 10, the density was low and the hardness was accordingly low. In Comparative Example 7, in which the sintering temperature was higher than that of Example 10, the density was slightly higher, but a decrease in hardness was observed that is presumably due to grain growth.

[0094] YF 3 In Example 11, a Y sintered at 900° C. was obtained according to the present disclosure, which has a relative density of 99.0% or more and a hardness of 5.0 GPa or more. 5 O 4 F 7A sintered body was obtained. It is clear that if the grain size of the raw material powder is made smaller than 0.5 μm, a sintered body with a relative density of 99.0% or more and a hardness of 5.0 GPa or more can be obtained even in a temperature range lower than 900°C. It is clear that in order to achieve a hardness of 5.0 GPa or more, the grain size should be at least 1.07 μm or less. Furthermore, the tan δ value of the sintered body according to this example is 1×10 -4 The less was better.

[0095] Focusing on tan δ in Examples 4 to 11 and Comparative Examples 5 to 7, all of the sintered bodies had sufficiently small values. -4 To achieve this, the density must be at least 95.8% or more, and 1×10 -4 In order to achieve the values ​​below these limits, it is necessary to make the density at least 96.8% or more.

[0096] As a result of XRD analysis of the sintered bodies of Examples 4 to 11 and Comparative Examples 5 to 7, the orthorhombic Y phase was found to be formed from the sintered bodies using the raw material powder A and the raw material powder B. 5 O 4 F 7 Only the orthorhombic Y phase was observed in the sintered compact using raw powder C. 5 O 4 F 7 and orthorhombic YF 3 Only the phases were detected, and no impurities were observed.

[0097] <3. Evaluation results of sintered bodies produced by hot press molding> Fig. 8 shows the manufacturing conditions and evaluation results of the sintered bodies produced by the example of the manufacturing method of the sintered body by hot press molding. Specifically, Fig. 8 shows the manufacturing conditions and evaluation results of the sintered bodies produced in Examples 12 to 19 and Comparative Examples 8 to 14.

[0098] Comparing Example 13 with Comparative Example 8, and Example 14 with Example 16, which are combinations of raw material powder A and raw material powder B sintered under the same conditions, Example 13 and Example 16, which used raw material powder A, have higher density and hardness. This is thought to be because the raw material powder has a small particle size, which allows the sintering temperature to be lowered, resulting in a higher density.

[0099] When comparing the combinations of raw powder B and raw powder C sintered under the same conditions, raw powder C generally tends to have a higher density. This is because 3 This is believed to be because the sintering temperature was lowered by the addition of

[0100] In Examples 13 and 14, raw material powder A was used and sintered at 750 to 800°C to obtain sintered bodies with a relative density of 99.0% or more and a hardness of 6.0 GPa or more. In Example 12, raw material powder A was used and sintered at 700°C to obtain sintered bodies with a relative density of 97.0% or more and a hardness of 6.0 GPa or more. 5 O 4 F 7 It is clear that if the grain size of the raw material powder is made smaller than 0.3 μm, a sintered body with a relative density of 97.0% or more and a hardness of 6.0 GPa or more can be obtained even in a temperature range lower than 700 to 800°C. Furthermore, the tan δ values ​​of the sintered bodies in these examples were all less than 10×10 -4 It can be seen that in order to achieve a hardness of 5.0 GPa or 6.0 GPa or more, the grain size should be at least 0.42 μm or less.

[0101] Y having a relative density of 97.0% or more and a hardness of 6.0 GPa or more in Example 15, which was sintered at 780°C using raw material powder B 5 O 4 F 7 In addition, the raw material powder B was used and sintered at 800 to 850° C. in Examples 16 and 17, and the Y compacts had a relative density of 99.0% or more and a hardness of 5.0 GPa or more. 5 O 4 F 7Sintered bodies were obtained in each example. It is clear that if the grain size of the raw material powder is made smaller than 0.5 μm, sintered bodies with sufficiently high relative density and hardness can be obtained even in the temperature range lower than 780 to 850°C. It is clear that in order to achieve a hardness of 5.0 GPa or more, the grain size should be at least 0.89 μm or less, and in order to achieve a hardness of 6.0 GPa or more, the grain size should be at least 0.57 μm or less. Furthermore, the tan δ values ​​of the sintered bodies in these examples were 1×10 -4 The density was low in Comparative Example 8, in which the sintering temperature was lower than that of Example 15. In Comparative Examples 9 and 10, in which the sintering temperature was higher than that of Example 17, the density was high, but a decrease in hardness was observed, which was probably due to grain growth.

[0102] YF 3 In Examples 18 and 19, raw material powder C containing the additive Y was sintered at 750 to 800°C, and the relative density was 99.0% or more and the hardness was 5.0 GPa or more. 5 O 4 F 7 Sintered bodies were obtained in each example. It is clear that if the grain size of the raw material powder is made smaller than 0.5 μm, a sintered body with a relative density of 99.0% or more and a hardness of 5.0 GPa or more can be obtained even in a temperature range lower than 750 to 800°C. It is clear that in order to achieve a hardness of 5.0 GPa or more, the grain size should be at least 0.49 μm or less. Furthermore, the tan δ value of the sintered body according to this example is 1×10 -4 The less was better.

[0103] Focusing on tan δ in Examples 12 to 19 and Comparative Examples 8 to 14, all sintered bodies except for Comparative Examples 8 and 11, which had low density, had sufficiently small values. -4 To achieve this, the density must be at least 98.1% or more, and 1×10 -4 In order to achieve these values, it is necessary to make the density at least 98.4% or more.

[0104] As a result of XRD analysis of the sintered bodies of Examples 12 to 19 and Comparative Examples 8 to 14, the orthorhombic Y crystal structure was found to be formed from the sintered bodies using raw material powder A and raw material powder B.5 O 4 F 7 Only the orthorhombic Y phase was observed in the sintered compact using raw powder C. 5 O 4 F 7 and orthorhombic YF 3 Only the phases were detected, and no impurities were observed.

[0105] <4. Consideration of physical properties> <4-1. Effect of particle size on hardness> Generally, the higher the density, the greater the hardness. However, when the relative density is 97.0% or more as in the sintered body according to the present disclosure, the grain size has a greater effect on the hardness than the relative density.

[0106] The Hall-Petch law is known to represent the relationship between grain size and hardness, and is known to be applicable to many metal materials. However, it is said that the Hall-Petch law is theoretically inapplicable to ceramics such as the sintered body of the present disclosure. Looking at the examples and comparative examples of the present disclosure, it is not possible to strictly determine whether the Hall-Petch law is applicable, but at least it is clear that, like the Hall-Petch law, the smaller the grain size, the greater the hardness tends to be. Therefore, the grain size of the sintered body of the present disclosure will be considered. In general, the hardness of a sintered body is thought to be greatly influenced by the composition of the material, so consideration was given to each raw material powder. As mentioned above, raw material powder A and raw material powder B have a grain size of Y 5 O 4 F 7 The raw material powder C consists of only Y 5 O 4 F 7 and Y.F. 3 It is a mixture of.

[0107] <4-1-1. Grain size that satisfies hardness of 5.0 GPa or more> As shown in FIG. 6, when the grain size of the sintered body produced by pressureless sintering of raw material powder C was at least 1.27 μm, the hardness of the sintered body was 5.0 GPa or more.

[0108] As shown in Fig. 7, when the grain size of the sintered body produced by spark plasma sintering raw material powder A is at least 1.15 μm, the hardness of the sintered body is 5.0 GPa or more. When the grain size of the sintered body produced by spark plasma sintering raw material powder B is at least 0.86 μm, the hardness of the sintered body is 5.0 GPa or more. When the grain size of the sintered body produced by spark plasma sintering raw material powder C is at least 1.07 μm, the hardness of the sintered body is 5.0 GPa or more.

[0109] As shown in Fig. 8, when the grain size of the sintered body produced by hot-press molding raw material powder B is at least 0.89 μm or less, the hardness of the sintered body is 5.0 GPa or more. When the grain size of the sintered body produced by hot-press molding raw material powder C is at least 0.49 μm or less, the hardness of the sintered body is 5.0 GPa or more.

[0110] From the above results, mainly Y 5 O 4 F 7 In the sintered body according to the present disclosure, the grain size at which the hardness is 5.0 GPa or more is at least 1.15 μm or less, preferably 0.86 μm or less. 3 Y is added 5 O 4 F 7 In the sintered body according to the present disclosure, the grain size at which the hardness is 5.0 GPa or more is at least 1.27 μm or less, and preferably 0.49 μm or less.

[0111] <4-1-2. Grain size that satisfies hardness of 6.0 GPa or more> As shown in FIG. 6, when the grain size of the sintered body produced by pressureless sintering of raw material powder A was at least 0.42 μm or less, the hardness of the sintered body was 6.0 GPa or more.

[0112] As shown in FIG. 7, when the grain size of the sintered body produced by spark plasma sintering raw material powder A was at least 1.05 μm or less, the hardness of the sintered body was 6.0 GPa or more.

[0113] As shown in Fig. 8, when the grain size of the sintered body produced by hot-press molding raw material powder A is at least 0.42 μm or less, the hardness of the sintered body is 6.0 GPa or more. When the grain size of the sintered body produced by hot-press molding raw material powder B is at least 0.57 μm or less, the hardness of the sintered body is 6.0 GPa or more.

[0114] From the above results, mainly Y 5 O 4 F 7 In the sintered body according to the present disclosure, the grain size at which the hardness is 6.0 GPa or more is at least 1.05 μm or less, preferably 0.42 μm or less. 3 Y is added 5 O 4 F 7 In the sintered body according to the present disclosure, the grain size at which the hardness is 6.0 GPa or more is at least 1.27 μm or less, and preferably 0.49 μm or less.

[0115] <4-2. Effect of density on tan δ> In dielectric materials, it is generally said that tan δ is greatly influenced by the state of grain boundaries, specifically, the state of additives and impurities that aggregate at the grain boundaries, and voids present inside the sintered body. Therefore, the tan δ of the sintered body according to the present disclosure was considered with a focus on the sintering method and density.

[0116] <4-2-1.tan δ, 10×10 -4 Density that satisfies > As shown in FIG. 6, when the density of the sintered body produced by pressureless sintering of raw material powders A, B, or C is at least 96.3%, its tan δ is 10×10 -4 The results were as follows.

[0117] As shown in FIG. 7, when the density of the sintered body produced by spark plasma sintering the raw material powders A, B, or C is at least 95.8%, the tan δ is 10×10 -4 The results were as follows.

[0118] As shown in FIG. 8, when the density of the sintered body produced by hot pressing raw material powder A, B, or C is at least 98.1%, its tan δ is 10×10 -4 The results were as follows.

[0119] From the above results, in the sintered body according to the present disclosure, tan δ is 10×10 -4 The density below this level can be said to be at least 95.8% or more, and preferably 98.1% or more.

[0120] <4-2-2. tan δ, 1×10 -4 Density that satisfies > As shown in FIG. 6, when the density of the sintered body produced by pressureless sintering of raw material powders A, B, or C is at least 96.3%, its tan δ is 1×10 -4 The results were as follows.

[0121] As shown in FIG. 7, when the density of the sintered body produced by spark plasma sintering the raw material powders A, B, or C is at least 96.8%, the tan δ is 1×10 -4 The results were as follows.

[0122] As shown in FIG. 8, when the density of the sintered body produced by hot pressing raw material powder A, B, or C is at least 98.4%, its tan δ is 1×10 -4 The results were as follows.

[0123] From the above results, it can be seen that the sintered body according to the present disclosure has a tan δ of 1×10 -4 The density below this level is at least 96.3% or more, and preferably 98.4% or more. As described above, from the viewpoint of dust generation, a higher density is preferable, and specifically, the density is at least 97.0% or more, and preferably 99.0% or more.

[0124] <5. Evaluation results of plasma resistance test of sintered body> FIG. 9 shows the results of a plasma resistance test of the sintered body.

[0125] In addition, in Comparative Example 15, a commercially available product manufactured by Kyocera Corporation, Y 2 O 3 The sintered body is a sintered body (model number: YO100A). For comparison, Y according to Comparative Example 15 is 2 O 3 The sintered body was similarly subjected to a plasma resistance test. The relative density and hardness of Comparative Example 15 are the values ​​in the manufacturer's catalog. 2 O 3 This is the value obtained by dividing the theoretical density by the theoretical density.

[0126] As shown in FIG. 9, the sintered body according to the embodiment has a Y 2 O 3 Compared to the sintered body, the amount of etching was equal to or smaller, and the change in surface roughness was also small. 5 O 4 F 7 The sintered body is Y 2 O 3 Compared to the sintered body, it has high plasma resistance overall, and is particularly advantageous in terms of reducing the amount of dust, which is the most important factor. In particular, the sintered bodies according to the examples using raw material powder A and raw material powder B are 2 O 3 It was found that compared to sintered bodies, the change in surface roughness was less than one-third, and this had a significant effect in reducing the size of particles generated.

[0127] The sintered body according to Comparative Example 11, which had a relative density of less than 97%, had a larger etching amount and a larger Ra deterioration rate than the sintered bodies according to the Examples. Also, the sintered bodies according to Comparative Examples 4, 10, and 12, which had a hardness of less than 5.0 GPa, had a larger etching amount and a larger Ra deterioration rate than the sintered bodies according to the Examples.

[0128] (Effects of the Invention) According to this disclosure, 5 O 4 F 7 The sintered body is Y 2 O 3 Compared to sintered bodies, the Y has a lower reactivity to halogen gas, so chemical corrosion is suppressed. 5 O 4 F 7The sintered body is Y 2 O 3 Since it has a high density equivalent to that of a sintered body and a hardness equivalent to or greater than that of the sintered body, physical corrosion is also suppressed. 5 O 4 F 7 The sintered body is Y 2 O 3 It is expected to be a next-generation corrosion-resistant material that will replace Y. 5 O 4 F 7 Since the sintered body has a small value of tan δ, the heat generated by the member is small and the plasma state is stable. 5 O 4 F 7 The sintered body has advantages such as power saving by reducing power loss, stabilization of etching rate, reduction of etching unevenness, labor saving for tuning, and prevention of plasma dispersion.

[0129] (Y 5 O 4 F 7 and yttrium oxyfluoride powder) Next, the yttrium oxyfluoride powder will be described. Fig. 10 is a graph showing peak intensities of yttrium oxyfluoride powder X-ray diffraction according to ICDD (International Centre for Diffraction Data).

[0130] In this disclosure, "Y 5 O 4 F 7 The substances marked with "Y" were found to be 5 O 4 F 7 Yttrium oxyfluoride is a substance that has been identified as "yttrium oxyfluoride". Y, O, and F are known to be compounds in various ratios. 5 O 4 F 7 The elemental composition and crystal structure of these yttrium oxyfluorides are similar to those of the yttrium oxide fluoride sintered bodies of the present disclosure. 5 O4 F 7 It is obvious that the same effect is obtained.

[0131] For example, according to the powder X-ray diffraction pattern database by the International Centre for Diffraction Data (ICDD), the Y 5 O 4 F 7 Compounds with a structure similar to that of Y 6 O 5 F 8 , Y 7 O 6 F 9 , Y 17 O 14 F 23 , Y 1 O 0.826 F 1.348 The X-ray diffraction peaks of these yttrium oxyfluoride powders listed in the database are shown in FIG. 10. In FIG. 10, when the maximum peak of each substance is set to 100, peaks with a value less than 1 are not plotted. As shown in FIG. 10, 5 O 4 F 7 It can be seen that the X-ray diffraction peaks of these five yttrium oxyfluorides, including , are very similar in peak position and peak intensity. For example, the 2θ value of the maximum peak is Y 5 O 4 F 7 , Y 6 O 5 F 8 , Y 7 O 6 F 9 , Y 17 O 14 F 23 , Y 1 O 0.826 F 1.348 The angles are close to each other, at 28.11°, 28.14°, 28.14°, 28.14°, and 28.13°, respectively. In actual X-ray diffraction measurements, the peak intensity changes and the peak position shifts depending on the condition of the measured sample and the measurement error of the instrument, so it is practically difficult to completely identify these five substances.

[0132] For the above reasons, the present disclosure 5 O 4 F 7 " includes these similar yttrium oxyfluorides.

[0133] In general, in the manufacture of ceramics, additives, so-called "auxiliaries," are added in amounts of several wt % to several tens of wt % in addition to the base material and then sintered to improve sinterability and control the microstructure of the sintered body. For example, Non-Patent Document 5 discloses a method of adding rare earths to control the microstructure of SiAlON ceramics and reduce the grain size to improve optical properties.

[0134] In the embodiments of the present disclosure, YF 3 However, even if the auxiliary agent disclosed in Non-Patent Document 5 is used, the effect is not as good as that of YF 3 It is obvious that the same effect is achieved when such an auxiliary is included. 5 O 4 F 7 It is defined as "consisting of". The particle size can be controlled by using an auxiliary agent to reduce dust generation. By reducing the particle size, the hardness can be increased and the physical corrosion resistance can be improved, as in the examples of the present disclosure. In addition, by reducing the diameter, the size of the particles generated can be reduced.

[0135] In the present disclosure, the material used as the auxiliary is Y 5 O 4 F 7 Similarly, it is desirable that the plasma resistance is high. In general, rare earth elements (Sc, La, Ce, Pr, Nd, Pm, SM, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu) have a relatively low vapor pressure when combined with halogens compared to other elements, and have excellent plasma resistance. Oxides, fluorides, and oxyfluorides, which are stable compounds of these elements, are preferred as auxiliary agents to be added in the present invention.

[0136] (Embodiment 4) Next, a description will be given of a semiconductor manufacturing equipment member and a method for manufacturing the same according to the fourth embodiment. Fig. 11 is a flow chart showing a method for manufacturing the semiconductor manufacturing equipment member according to the fourth embodiment.

[0137] The semiconductor manufacturing equipment member according to the fourth embodiment is a plasma equipment member using a sintered body. The sintered body is a sintered body according to the first embodiment, and a sintered body manufactured using the manufacturing method for a sintered body according to the first to third embodiments. The plasma equipment member is, for example, an edge ring, a shower nozzle, or a window. The window is a member that transmits at least radio waves.

[0138] First, a sintered body is manufactured (step ST101). Specifically, the sintered body is manufactured by using the manufacturing method for a sintered body according to any one of the first to third embodiments.

[0139] Furthermore, the sintered body manufactured in step ST101 is applied to a plasma device member (step ST102). The plasma device member can be used as a semiconductor manufacturing equipment member. In this manner, the semiconductor manufacturing equipment member can be manufactured.

[0140] (Embodiment 5) Next, a description will be given of a semiconductor manufacturing apparatus and a manufacturing method thereof according to the fifth embodiment. Fig. 12 is a flow chart showing the manufacturing method of the semiconductor manufacturing apparatus according to the fifth embodiment.

[0141] The semiconductor manufacturing equipment according to the fifth embodiment is configured to include the member for a semiconductor device according to the fourth embodiment described above.

[0142] First, a semiconductor manufacturing equipment member is manufactured (step ST201). Specifically, the semiconductor manufacturing equipment member is manufactured using the method for manufacturing a semiconductor manufacturing equipment member according to the fourth embodiment.

[0143] Next, the semiconductor device member manufactured in step ST201 is applied to a semiconductor manufacturing equipment (step ST202). In this manner, the semiconductor manufacturing equipment member can be manufactured.

[0144] The present invention is not limited to the above-described embodiment, and can be modified as appropriate without departing from the spirit and scope of the present invention. [Explanation of symbols]

[0145] ST11, ST12, ST13, ST14, ST15, ST16, ST21, ST22, ST31, ST32, ST33, ST101, ST102, ST201, ST202 Steps

Claims

1. A sintered body containing 50% by mass or more of yttrium oxyfluoride, having a relative density of 97.0% or more, and having a Vickers hardness of 5.0 GPa or more.

2. The sintered body according to claim 1 , further comprising a fluoride of yttrium.

3. 3. The sintered body according to claim 1, comprising at least one of a rare earth oxide, a rare earth fluoride, and a rare earth oxyfluoride in an amount of 10 mass % or less.

4. The sintered body according to any one of claims 1 to 3, having a relative density of 99.0% or more.

5. 5. The sintered body according to claim 1, 3, or 4, wherein the average grain size of the crystal grains constituting the sintered body is 1.15 [μm] or less.

6. The sintered body according to any one of claims 2 to 4, wherein the average grain size of the crystal grains constituting the sintered body is 1.27 μm or less.

7. The dielectric tangent (tan δ) measured at 1 MHz is 10 x 10 -4 The sintered body according to any one of claims 1 to 6, wherein:

8. A member for a plasma device, comprising the sintered body according to any one of claims 1 to 7.

9. The member for a plasma apparatus according to claim 8 , wherein the member for a plasma apparatus is an edge ring, a shower nozzle, or a window.

10. A semiconductor manufacturing apparatus comprising the member for a plasma apparatus according to claim 8 or 9.

11. A method for manufacturing a sintered body, comprising the steps of: molding a molded body containing yttrium oxyfluoride powder having a particle size of 0.3 μm or less; and forming a sintered body by atmospheric sintering the molded body at 800° C. or less.

12. A method for manufacturing a sintered body, comprising the steps of: molding a molded body containing yttrium oxyfluoride powder and yttrium fluoride powder having a particle size of 0.5 μm or less; and forming a sintered body by atmospheric sintering the molded body at 850° C. or less.

13. A method for manufacturing a sintered body, comprising the steps of: using a raw material powder containing yttrium oxyfluoride powder having a particle size of 0.5 μm or less; and sintering the raw material powder at 850° C. or less by a spark plasma sintering (SPS) method to form a sintered body.

14. The method for producing a sintered body according to claim 13, wherein the particle size of the yttrium oxyfluoride powder is 0.3 μm or less, and the sintered body is formed by sintering at 800° C. or less by the SPS method.

15. A method for producing a sintered body, comprising the steps of: using raw material powder containing yttrium oxyfluoride powder having a particle size of 0.5 μm or less and yttrium fluoride powder; and sintering the raw material powder at 900° C. or less by a spark plasma sintering (SPS) method.

16. A method for producing a sintered body, comprising the steps of: using a raw material powder containing yttrium oxyfluoride powder having a particle size of 0.5 μm or less; and sintering the raw material powder at 850° C. or less by a hot press method to form a sintered body.

17. The method for producing a sintered body according to claim 16, wherein the particle size of the yttrium oxyfluoride powder is 0.3 μm or less, and the sintered body is formed by sintering at 800° C. or less by the hot pressing method.

18. A method for producing a sintered body, comprising the steps of: using raw material powder containing yttrium oxyfluoride powder having a particle size of 0.5 μm or less and yttrium fluoride powder; and sintering the raw material powder at 800° C. or less by a hot press method to form a sintered body.

19. A method for producing a sintered body using the method for producing a sintered body according to any one of claims 11 to 18, and then applying the sintered body to a plasma device member.

20. The method for producing a member for a semiconductor manufacturing equipment according to claim 19, wherein the member for a plasma equipment is an edge ring, a shower nozzle, or a window.

21. 21. A method for manufacturing a semiconductor manufacturing equipment member, further comprising the step of manufacturing a semiconductor manufacturing equipment member by using the method for manufacturing a semiconductor manufacturing equipment member according to claim 19 or 20, and then applying the semiconductor manufacturing equipment member to a semiconductor manufacturing equipment.

Citation Information

Patent Citations

  • Sintered body

    JP2016098143A

  • Sintered body

    JP2016153369A

  • Method for forming yttrium fluoride oxide coating film and yttrium fluoride oxide coating film obtained by the method

    JP2020525640A

  • Film-forming material and film

    WO2018083854A1

  • Sintered body

    WO2020179296A1